1991
DOI: 10.1080/11250009109355755
|View full text |Cite
|
Sign up to set email alerts
|

Macronuclear DNA and total protein content variations inParamecium primaureliaexconjugant clones

Abstract: Cytofluorometric analyses of the macronuclear DNA content (MDC) and total protein content (TPC) of Paramecium primaurelia stock 90 were carried out in cells at successive ages, from 10 to 26 fissipns . after conjugation, during immaturity and transition to maturity. Between the 10th and the 20th exconjugant fission within the immaturity period, MDC decreases to a minimum whereas TPC remains constant. Following the 20th fission during the transition period TPC decreases, and from the 22nd to the 26th fission bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1991
1991
1993
1993

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…On the other hand, when the macronuclear DNA content decreases as clonal age increases (Kimball, 1967;Smith-Sonneborn & Klass, 1974;Schwartz & Meister, 1975;Klass & Smith-Sonneborn, 1976;Delmonte Corrado et al, 1986;Delmonte Corrado & Margallo, 1991), a higher rate of food vacuole formation is needed to provide precursors for the overall synthesis. Food vacuole formation can remain high as long as the macronuclear DNA content is in excess.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, when the macronuclear DNA content decreases as clonal age increases (Kimball, 1967;Smith-Sonneborn & Klass, 1974;Schwartz & Meister, 1975;Klass & Smith-Sonneborn, 1976;Delmonte Corrado et al, 1986;Delmonte Corrado & Margallo, 1991), a higher rate of food vacuole formation is needed to provide precursors for the overall synthesis. Food vacuole formation can remain high as long as the macronuclear DNA content is in excess.…”
Section: Discussionmentioning
confidence: 99%
“…Especially, since previous studies (Crippa Franceschi et al, 1979;Delmonte Corrado et al, 1986;Ramoino et al, 1988) on temperature resistance and macronuclear DNA content during clonal development have revealed remarkable changes, that could not be recognized when testing was spaced, but only when the analysis was carried out at short fission intervals. Temperature resistance showed an oscillatory pattern during clonal life (Crippa Franceschi et al, 1979;Ramoino et al, 1988), and the macronuclear DNA content decreased in young clonal cells, but this decrease was not constant and showed temporary resumption (Delmonte Corrado et al, 1986;Delmonte Corrado & Margallo, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…The TPC was measured in the following cell types: (i) 14-and 12-fission-old cells of exconjugant and exautogamous clones, respectively, growing in log-phase and sampled within 10 min from their division; (ii) mating reactive cells of both exconjugant and exautogamous clones, separated from loosely united pairs by means of the «split pair» method (Hiwatashi, 1951); (iii) cells undergoing autogamy at the ages of 25 and 33 fissions after conjugation. The method for calculating the cell age in fissions is described in Delmonte Corrado & Margallo (1991).…”
Section: Methodsmentioning
confidence: 99%
“…In a cytofluorometric study of P. primaurelia, stock 9Q, it was shown that cells of clones maintained in loggrowth phase contain a total amount of protein that is significantly higher during immaturity than in maturity (Delmonte Corrado & Margallo, 1991). Should this difference be relevant to the acquisition of the cell mating competence, one may presume that exautogamous clones lacking immaturity have a lower total protein content (hereafter abbreviated as "TPC") than that of immature exconjugant clones.…”
Section: Introductionmentioning
confidence: 99%